THE EFFECT OF LEGAL REGULATION ON CONSUMER TRUST IN SHOPPING ON THE E-COMMERCE PLATFORM SHOPEE - Siti Junaidah Hasibuan; Hasibuan, Siti Junaidah; Fransiscus, Raymond; Nasution, Hafni Cholida (Manajemen: Jurnal Ekonomi, 2025)
This study aims to analyze the effect of legal regulation on consumer trust in shopping on the e-commerce platform Shopee. The research employed a quantitative approach with a survey method. The population included all Shopee consumers who had made at least one transaction within the last six months. The sample size was determined using Hair et al.’s formula, resulting in 45 respondents. Data were analyzed using classical assumption tests and simple linear regression with the assistance of SPSS version 26. The findings reveal that legal regulation has a positive and significant effect on consumer trust in shopping on Shopee. This indicates that the better the implementation and enforcement of legal regulations such as consumer protection, personal data security, and legal certainty in electronic transactions the higher the level of consumer trust in conducting online transactions through Shopee